FORMULATION AND TEST OF ANTIBACTERIAL ACTIVITY OF EMULGEL ESSENTIAL OIL OF CITRONELLA (CYMBOPOGON NARDUS (L.) RENDLE) AND ALOE VERA (ALOE VERA (L.) BURM. F.) EXTRACT AGAINST PROPIONIBACTERIUM ACNES - Ratna Dewi, Sinta; Ressandy, Sylvan Septian; Handoko, Lidya; Pratiwi, Jati; Rahmah, Widya (Faculty of Vocational Studies, Universitas Airlangga, 2023)
Background: Acne is described as an abnormal skin condition caused by the disruption of excess oil production and collaboration with bacteria. Aloe vera and citronella oil are plants that have antibacterial properties, including acne-causing bacteria. Purpose: To obtain a formulation that has an anti-acne effect. Method: This research method is experimental in which the formulation of citronella oil emulgel and aloe vera extract is made as much as 10-15 grams in each formula by varying the additional ingredients in each formulation. This formula was made from three different concentrations (F1 (6%:4%), F2 (4%:6%), and F3 (5%:10%)) and tested the physical stability, among others, organoleptic, pH, homogeneity, dispersion and antibacterial activity against Propionibacterium acnes. Result: There was no significant difference between the organoleptic test, pH, homogeneity, and inclusion in the eligible category. In contrast, the dispersion test had a slight difference in F2 and F3, which did not meet the requirements. Conclusion: Inhibitory activity test of the preparations obtained the average diameter of citronella oil emulgel preparations and aloe vera extract at concentrations of F1 (6%:4%), F2 (4%:6%), and F3 (5%:10%) are 11 mm, 10.7 mm and 16 mm and the ability to inhibit bacteria by all concentrations was in a strong category. Among the three formulations known to have the most remarkable effectiveness was at F3 (5%:10%) with an inhibitory diameter of F3 16 mm.